(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Cataract is the main cause of visual impairment and treatable blindness in the world and surgery can restore normal sight to the patients. In bilateral cataract patient, surgery in the second eye is as important and meaningful as surgery in the first eye and it can be performed by immediate sequential (ISBCS) and delayed sequential bilateral cataract surgery (DSBCS). There is no statistically significant difference in surgical complications, visual acuity or long term self-perceived visual function between these two methods. To adopt surgical procedure, to improve the patient’s satisfaction and to improve the quality of services, patient opinion should be a great concern. This evaluative study was done to find out various recommendations and suggestions from patients regarding merits & demerits of both types of cataract surgery that will be helpful for the decision-maker and administrator for future practice of cataract surgery in Canada. In this study, vision related quality of life improved in both groups. Participants in DSBCS group experienced different types of difficulties during the gap period between first eye and second eye cataract surgery i.e. visual imbalance between the two eyes and difficulty in driving. They recommended and suggested that cataract surgery wait time should be reduced and the difficulties experienced during the gap period can be eliminated by adopting ISBCS procedure. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 07-13